Comment on â€œRisk Factors Associated With Low Birth Weightâ€ - Khanal, V (Journal of Nepal Health Research Council, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> In 2011 Oct issue, Journal of Nepal Health Research Council published an article â€œrisk factors associated with low birth weightâ€ by Yadav DK affiliated to School of Health and Allied Sciences, Pokhara University, Chaudhary U affiliated to Child Welfare Scheme, Kaski, and Shrestha N from CIST College, Kathmandu, Nepal. As a result, comments were sent to JNHRC, and are published below. Yadav DK, Chaudhary U, Shrestha N. Risk Factors Associated with Low Birth Weight. J Nepal Health Res Counc 2011 <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Oct;9(19):159-64. PMID: 22929846.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>